Teologi Al-Ma'un dan Gerakan Islam Berkemajuan: Rekonstruksi Pemikiran KH Ahmad Dahlan dalam Muhammadiyah - Apris Yaman; Desi Asmaret; Julhadi; Syaifullah (Journal of Social, Educational and Religious Studies, 2026)
This study aims to analyze the thought of KH Ahmad Dahlan in shaping the Islamic reform movement through Muhammadiyah, focusing on the concepts of tajdid, Al-Ma’un theology, and their relevance to the development of Progressive Islam. The research employed a qualitative approach using a library research method based on primary and secondary sources related to KH Ahmad Dahlan’s thought, the history of Muhammadiyah, and scholarly studies on Islamic reform in Indonesia. Data were analyzed through content analysis and a historical-interpretative approach to examine the relationship between religious ideas, social transformation, and the institutionalization of Islamic movements. The findings reveal that Ahmad Dahlan’s concept of tajdid was not limited to the purification of Islamic beliefs and practices but was also directed toward social transformation through education, healthcare services, philanthropy, and community empowerment. Al-Ma’un theology served as the primary foundation linking individual piety with social responsibility, which was subsequently manifested through Muhammadiyah’s various charitable and social institutions. The study concludes that KH Ahmad Dahlan’s thought represents a model of transformative Islam that integrates spirituality, rationality, and social concern. This model remains highly relevant in addressing contemporary challenges, including educational development, social inequality, digital transformation, and the strengthening of religious moderation.